Current‐Driven Organic Electrochemical Transistors for Monitoring Cell Layer Integrity with Enhanced Sensitivity. Issue 19 (26th July 2021) - Lieberth, Katharina; Romele, Paolo; Torricelli, Fabrizio; Koutsouras, Dimitrios A.; Brückner, Maximilian; Mailänder, Volker; Gkoupidenis, Paschalis; Blom, Paul W. M.
Abstract: In this progress report an overview is given on the use of the organic electrochemical transistor (OECT) as a biosensor for impedance sensing of cell layers. The transient OECT current can be used to detect changes in the impedance of the cell layer, as shown by Jimison et al. To circumvent the application of a high gate bias and preventing electrolysis of the electrolyte, in case of small impedance variations, an alternative measuring technique based on an OECT in a current‐driven configuration is developed. The ion‐sensitivity is larger than 1200 mV V ‐1 dec ‐1 at low operating voltage. It can be even further enhanced using an OECT based complementary amplifier, which consists of a p‐type and an n‐type OECT connected in series, as known from digital electronics. The monitoring of cell layer integrity and irreversible disruption of barrier function with the current‐driven OECT is demonstrated for an epithelial Caco‐2 cell layer, showing the enhanced ion‐sensitivity as compared to the standard OECT configuration. As a state‐of‐the‐art application of the current‐driven OECT, the in situ monitoring of reversible tight junction modulation under the effect of drug additives, like poly‐l ‐lysine, is discussed. This shows its potential for in vitro and even in vivo toxicological and drug delivery studies. Abstract : The organic electrochemical transistor (OECT) used as a biological barrier sensor offers numerous advantages (biocompatibility, mechanical flexibility, and in situ monitoring) for biomedical applications.The fast and promising progress in research on current‐driven OECTs, having the assets to operate with high sensitivity at low voltage and to obtain the results as direct output, has a high impact on monitoring integrated tissue.